The Effect Of Using Cake Application As Learning Media Into Students’ Speaking Ability At The Eighth Grade Of Smp Negeri 37 Medan - Sihite, Agustina; Pakpahan, Carolina; Saragi, Christina Natalina (Lembaga Riset dan Inovasi Almatani, 2024)
The purpose of this study was to obtain empirical data on the effect of using cake Application as Learning Media into students' ability to practice their language skills. This study was conducted using an experimental quantitative method. The sample was 40 students from eight classes at SMP Negeri 37 Medan. The sample was VIII A as the experimental class and VIII B as the control class. In the experimental class, the researcher used as a teaching media cake application while in the control class, the researcher used conventional methods in the learning process. The instrument of this study was a speaking test that we divided into pre-tests and post-tests. The data obtained from the test were analyzed using the SPSS20 program. The average pre-test score in the experimental class was 64,35, and the post-test score was 78,35. The average pre-test score in the control group was 65,2 and the post-test score 75,5. This shows that the average score in the experimental group was higher than the control group. The result was t-calculated > t -table with a significance level of p = 0.05 (3272 > 2192) The alternative hypothesis (Ha) was accepted, and the null hypothesis (Ho) was rejected. It also proved that English subject teachers apply the Cake Application as an alternative teaching medium to help the speaking ability of class VIII students at SMP Negeri 37 Medan.